Assessing Bleeding Risk in Atrial Fibrillation Patients: Comparing a Bleeding Risk Score Based Only on Modifiable Bleeding Risk Factors against the HAS-BLED Score. The AMADEUS Trial - Esteve-Pastor, María Asunción; Rivera-Caravaca, José Miguel; Shantsila, Alena; Roldán, Vanessa; Lip, Gregory Y. H.; Marín, Francisco (Thrombosis and Haemostasis, 2017)
Background The HAS-BLED (hypertension, abnormal renal/liver function, previous stroke, bleeding history or predisposition, labile international normalized ratio [INR], elderly and drugs/alcohol consumption) score has been validated in several scenarios but the recent European guidelines does not recommend any clinical score to assess bleeding risk in atrial fibrillation (AF) patients and only focus on modifiable clinical factors.Purpose The aim of this study was to test the hypothesis that the HAS-BLED score would perform at least similarly to an approach only based on modifiable bleeding risk factors (i.e. a ‘modifiable bleeding risk factors score’) for predicting bleeding events.Methods We performed a comparison between the HAS-BLED score and the new ‘modifiable bleeding risk factors score’ in a post hoc analysis in 4,576 patients included in the AMADEUS trial.Results After 347 (interquartile range, 186–457) days of follow-up, 597 patients (13.0%) experienced any clinically relevant bleeding event and 113 (2.5%) had a major bleeding. Only the HAS-BLED score was significantly associated with the risk of any clinically relevant bleeding (Cox's analysis for HAS-BLED ≥ 3: hazard ratio 1.38; 95% confidence interval [CI], 1.10–1.72; p = 0.005). The ‘modifiable bleeding risk factors score’ ≥ 2 were non-significantly associated with any clinical relevant bleeding. The two scores had modest ability in predicting bleeding events. The HAS-BLED score performed best in predicting any clinically relevant bleeding (c-indexes for HAS-BLED, 0.545 [95% CI, 0.530–0.559] vs. the ‘modifiable bleeding risk factors score’, 0.530 [95% CI, 0.515–0.544]; c-index difference 0.015, z-score = 2.063, p = 0.04). The HAS-BLED score with one, two and three modifiable factors performed significantly better than the ‘modifiable bleeding risk factors scores’ with one, two and three modifiable risk factors.Conclusion When compared with an approach only based on modifiable bleeding risk factors proposed by European Society of Cardiology (ESC) AF guidelines, the HAS-BLED score performed significantly better in predicting any clinically relevant bleeding in this clinical trial cohort. While modifiable bleeding risk factors should be addressed in all AF patients, the use of a formal bleeding risk score (HAS-BLED) has better predictive value for bleeding risks, and would help decision-making in identifying ‘high risk’ patients for scheduling reviews and follow-up.
Keywords: atrial fibrillation; guideline; risk score; haemorrhage; vitamin k antagonist